Risiko Stunting pada Pasien Diabetes Mellitus - Emy Rianti (Politeknik Kesehatan Tanjung Karang, 2017)
In the last decade, more evidence that malnutrition at a very early age and occurs chronically or recurrently is an important risk of non-communicable diseases in adulthood, and one of them is diabetes mellitus. In addition, studies on the pattern of linear growth in Indonesia suggest that growth failure brings consequences of retained effects in later ages. Growth failure in infants and children is a benchmark for future short-term growth failure in adulthood. The objective of the study was to assess the factors that became the risk of adult stunting in patients with diabetes mellitus. The type of this research was quantitative with the analytic method through cross-sectional study design approach, involving 60 respondents, data were taken in Depok General Hospital of West Java, on September 2016, data taken in primary and secondary. Criteria for patients with diabetes mellitus were determined based on doctor's diagnosis, while weight, height, and economic status data were obtained through direct interview and measurement. Stunting was determined by WHO standards in 2006 and BMI was determined according to WHO standards in 2004. The results of this study indicate that there was a significant relationship between age with short-term patients with diabetes mellitus. A recommendation, need further research with a more controlled design to ensure the long-term impact of risk of non-communicable diseases as a response to malnutrition at an early age.